ANALISIS SWOT DALAM MENGEMBANGKAN UNIT USAHA PADA KOPERASI SYARIAH - Latifah, Eny; Auliyah, Lutfi; Al-Busthomi, Yazid; Azizah, Lailiyatul (JISEF : Journal Of International Sharia Economics And Financial, 2022)
The purpose of this study was to determine the development of existing business units in the sharia cooperative BMT Sunan Drajat by using SWOT analysis. The research method used is descriptive qualitative using data analysis that combines data triangulation to get results that are in accordance with reality. The results showed that the development of business units in the sharia cooperative of BMT Sunan Drajat included: Department Store, Garam Samudera, Laundry, Printing, Book & Photocopy Stores, Putra Putri Canteen, Sunan Drajat Islamic Boarding School Cooperative. Its strength is the strong collaboration between stakeholders, students, alumni and the community around Sunan Drajat, which has relatively cheap prices in each business unit, both goods and services provided. Threats faced are competitors who have digitization facilities and market share that has expanded first. The weakness in the development of business units is the lack of available resources that can be relied on as a whole so that in its implementation it is less than optimal, unable to keep up with existing technological advances so that it is less than optimal in the production process of goods and services.